Rethinking the in-between: Designing with a socio-ecological approach to activate the potential of Terrain Vague spaces - Iannizzotto, L. S.; Paio, A. (plaNext-Next Generation Planning, 2025)
Rapid and uncontrolled processes of urbanization expanded cities boundaries and generated a new type of space that can offer rare opportunities. These Terrain Vague spaces are abandoned and open spaces where urban, rural and wild dimensions mingle. They could play a significant role in addressing urgent urban socio-ecological challenges related to sustainable, resilient and inclusive development. These spaces have great value and potential as rare intersections of social and ecological interests. Despite their value, these spaces are constantly at risk of disappearing due to massive urban development pressures and the perception that they are problems to be solved rather than valued. To harness the enormous potential of Terrain Vague, a new approach is necessary. This paper aims to describe a new social-ecological approach that amplifies and activates the potential of Terrain Vague spaces, outlining principles derived from theory and academic literature, and verifying the emergence of projects in line with these principles. For this purpose, nine projects were chosen as case studies, with the aim of demonstrating the concrete implementation of theoretical principles to make an initial attempt at systematizing these projects, and finally, to identify some of the possible strategies implemented in the development of these specific cases.